Investigators at University of Malaya describe findings in ethanol - Asep, E. K.; Jinap, Selamat; Jahurul, Md. Haque Akanda; Sarker, Md. Zaidul Islam; Singh, Harbhajan (NewsRx LLC, 2014)
By a News Reporter-Staff News Editor at Life Science Weekly -- New research on Ethanol is the subject of a report. According to news originating from Kuala Lumpur, Malaysia, by NewsRx correspondents, research stated, "Cocoa butter was successfully extracted from cocoa liquor by supercritical carbon dioxide (SC-CO2) at 35 MPa, 60 degrees C and 2 mL/min with 5%, 15% and 25% cosolvents. The extraction yield of triglycerides (TG) and fatty acid (FA) compositions were significantly influenced by the concentration of polar cosolvents." ...